ANALISIS PERKEMBANGAN SOSIAL DAN EMOSIONAL ANAK TERHADAP HASIL BELAJAR ANAK - Karia Candra Hadiwilestari; Indah Lestari; Moch Widjanarko (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study aims to analyze the social and emotional development of fourth-grade students at SD Negeri 4 Tulakan based on the five domains of Social and Emotional Competence (SEC) through observation, supported by teacher interviews. The results indicate that students’ social-emotional development is in the fairly good category; however, several aspects still need improvement. Students are able to express emotions and cooperate with others, but they continue to experience difficulties in emotional regulation, time management, respecting turn-taking in conversations, and resolving minor conflicts. In the decision-making domain, students are fairly capable of considering their actions but are not yet consistent in accepting the consequences. These findings emphasize the need for more supportive learning strategies to optimize the development of students’ social-emotional competencies.